Enzymatic activity on sediments and nematode assemblage responses during seagrass beds habitat recovery following the disturbance of the traditional digging activity of bivalves harvesting. - Branco, J. (2017)
Sediment digging is an anthropogenic activity connected to the exploitation of living resources in estuarine and marine environments. The knowledge on the functional responses of the benthic assemblages to the physical disturbance is an important baseline to understand the ecological processes of the habitat recovery and restoration and to develop tools for the management of the harvesting activities. To investigate the effects of the digging activity of the bivalves on Zostera noltii seagrass beds a manipulative field experiment was conducted that included the enzymatic activity of sediments and the associated nematode assemblages. Four plots (two undisturbed serving as control and two dug to collect bivalves - treatment) with 18 subplots were randomly located at seagrass beds in the Mira estuary at the SW coast of Portugal. Samples were randomly and unrepeatably collected from three subplots of each plot in five different occasions, before sediment digging (T0) up to six months after disturbance (T5). Microbial activity in sediments was assess by determining the extracelular enzymatic activity of six hydrolytic enzymes (sulfatase, phosphatase, b -N-acetilglucosaminidase, b-glucosidase, urease, protease) and two oxidoreductases (phenol oxidase and peroxidase). The microbial community status was also assessed through the measurement of dehydrogenase, which reflects microbial respiration. The nematode assemblages composition, biodiversity and trophic composition at different sampling occasions were also analyzed. The fluorometric and biochemical parameters analysed of the Z. noltii plants during the experimental period showed a recovery of the seagrass beds, and it was detected an increase of the enzymatic activity of the sediments after disturbance. The nematodes assemblages were similar in all sampling occasions. The seagrass beds and the nematodes assemblages associated showed a high resilience to the stress caused by the traditional bivalves digging activity. The obtained results allow the development of a management programme for the commercial fishing activity to maintain the good environmental status and minimized the secondary environmental effects on marine and estuarine habitats through the establishment of a baseline for the regulation of the harvesting frequency.